2021
DOI: 10.1039/d1bm00973g
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of PEI-PEG-squalene-dsDNA polyplex formation: the delicate role of the PEG length in the binding of PEI to DNA

Abstract: The biocompatible hydrophilic polyethylene glycol (PEG) is widely used in biomedical applications, such as drug or gene delivery, tissue engineering or as antifouling in biomedical devices. Experimental studies have shown...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…[ 24 ] Furthermore, modification with long polymer chains also tends to weaken the inherent properties from PEIs. [ 25 ] Thermoresponsive PEIs with amide end groups were also prepared, but they exhibit a relative broad phase transitions. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24 ] Furthermore, modification with long polymer chains also tends to weaken the inherent properties from PEIs. [ 25 ] Thermoresponsive PEIs with amide end groups were also prepared, but they exhibit a relative broad phase transitions. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Among them, hyperbranched polymers, especially hyperbranched polyethyleneimines (PEIs), show higher solubility and lower viscosity than corresponding linear polymers, which is beneficial for their applications. [4,5] PEIs and their derivatives possess highly branched peripherals containing plenty of amino groups, which makes them widely used as polyprotic bases and polydentate ligands. [6,7] In addition, their active amino groups provide convenient ways for further modification to develop new derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another gold standard in non-viral gene delivery, high molecular weight (HMW) PEI also faces the quandary of being highly efficient in transfection and toxic at the same time [17][18][19]. Fortunately, PEI possesses abundant reactive amine groups for versatile functionalization and has the potential to be decorated as a stand-alone DNA condensing agent [20][21][22][23]. Interestingly, it has also been found that PEI can promote the nuclear entry of DNA for transcription while lipid-bound DNA is not transcription-active [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent counterions are present also in viruses, neutralizing the negatively-charged DNA and RNA macromolecules, and allowing them to pack densely inside the small volume of the viral capsid (Ames and Dubin, 1960;Roos et al, 2007;Carrivain et al, 2012;Mounce et al, 2017;Firpo and Mounce, 2020). The interactions of positively-charged PAs with DNA have a significant biological effect, and are also involved in some emerging biotechnological applications (Korolev et al, 2001;D'Agostino, 2018;Perepelytsya et al, 2019;Mocci et al, 2021;Vasiliu et al, 2021). The study of the role of PAs in the structural organization of DNA in living organisms is of paramount importance for the understanding of key biological functions.…”
Section: Introductionmentioning
confidence: 99%